Série de casos de cromomicose e esporotricose no Hospital Universitário de Santa Maria, Rio Grande do Sul, Brasil - Benvegnú, Ana Maria (2017)
Sporotrichosis and chromomycosis are deep fungal infections that affect the subcutaneous cellular tissue of acute-subacute and chronic evolution, respectively. Although they have a universal distribution, they present high incidence in tropical and subtropical areas, in which the Brazilian territory is inserted, where they have stood out due to the frequent epidemics that continue to occur. Objectives: To evaluate the incidence of chromomycosis and sporotrichosis and the profile of the patients affected by these diseases in the Santa Maria University Hospital (HUSM), Santa Maria, RS. Methods: A series of cases of chromomycosis and sporotrichosis confirmed by mycological examination were performed in the period from January 1, 2006 to December 31, 2015. Results: A total of 43 cases of sporotrichosis were diagnosed, predominantly young male adults and rural workers. The most described clinical form was cutaneolymphatic, locating predominantly in the upper limbs. A correlation between the cutaneolymphatic form and location in the upper limbs was observed as well as a correlation between the localized cutaneous form (second most described clinical form) and the occurrence in the lower limbs. Potassium iodide was the treatment of choice, with high cure rates. In relation to chromomycosis, 6 cases were found, mostly occurring in adult men working in rural areas. The lesions were mainly located in the upper limbs in clinical plaque form. Most patients required multiple forms of treatment, with only two being cured. Conclusion: This study updated the epidemiological situation of chromomycosis and sporotrichosis in the central region of the state of Rio Grande do Sul in the last decade.